2017
DOI: 10.22161/ijeab/2.3.21
|View full text |Cite
|
Sign up to set email alerts
|

In vitro free radical scavenging activity of different extracts of Adansonia digitata L.

Abstract: Abstract- (27.69 & 20) as measured by using DPPH assay. These results showed the antioxidant potential of this medicinal plant to make use in the preparation of drugs with free radical scavenging activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Positive correlations between phenolic compound concentrations and antioxidant activity have been recorded by numerous researchers (Konan et al 2014). The in vitro antioxidant activity of A. digitata (baobab) was well documented previously by Talari et al (2017) and Braca et al (2018). According to the present data, helium-neon laser treatment for A. digitata stems and leaves at the power of 10 mW for 2 min (T2) increased concentrations of investigated polyphenol compounds including gallic acid, coffeic acid, kaempferol, luteolin, rutin, quercetin, naringenin, catechin, dihydroxyisoflavone, and cinnamic acid compared to extract from the untreated plant (T1).…”
Section: Discussionsupporting
confidence: 62%
“…Positive correlations between phenolic compound concentrations and antioxidant activity have been recorded by numerous researchers (Konan et al 2014). The in vitro antioxidant activity of A. digitata (baobab) was well documented previously by Talari et al (2017) and Braca et al (2018). According to the present data, helium-neon laser treatment for A. digitata stems and leaves at the power of 10 mW for 2 min (T2) increased concentrations of investigated polyphenol compounds including gallic acid, coffeic acid, kaempferol, luteolin, rutin, quercetin, naringenin, catechin, dihydroxyisoflavone, and cinnamic acid compared to extract from the untreated plant (T1).…”
Section: Discussionsupporting
confidence: 62%
“…Besides, the leaves have an abundant amount of mucilage, carbohydrate (60-70%), protein (13-15%), fiber (11%), fat (4-10%), and minerals including calcium, iron, potassium, magnesium, phosphorous, zinc, and manganese [ 9 ]. Previously, Talari et al [ 10 ] had concluded that methanolic extract of various parts of the tree showed a strong free radical scavenging activity associated with their phytochemical constituents. This property raises the possibility that these methanolic extracts could be utilized in the preparation of antioxidant drugs for the treatment of a range of ailments [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Talari et al [ 10 ] had concluded that methanolic extract of various parts of the tree showed a strong free radical scavenging activity associated with their phytochemical constituents. This property raises the possibility that these methanolic extracts could be utilized in the preparation of antioxidant drugs for the treatment of a range of ailments [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The methanolic fruit pulp and leaf extracts of A. digitata exhibited in vitro antioxidant activities as studied by 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH), 2,2-azinobis—(3-ethylbenzothiazoline-6-sulfonate) (ABTS), ferric reducing antioxidant power (FRAP), β-carotene bleaching test, superoxide-scavenging assays [ 50 , 150 ]. The methanol extracts of leaf, seed, bark, fruit wall, and floral extracts of A. digitata were reported for their DPPH scavenging potential [ 147 ]. The DPPH scavenging activity was highest in seed extract (27.69%) and lowest in fruit wall (20.69%) extract.…”
Section: Pharmacological Potential Of Bombacoideaementioning
confidence: 99%